A cone‐beam computed tomography analysis of angulation and inclination of whole tooth and clinical crown in adults with normal occlusion. (15th July 2019) - Wang, Honghong; Zhao, Ning; Li, Peilun; Shen, Gang
Abstract: Objectives: To identify the mesiodistal angulation and faciolingual inclination of whole tooth and clinical crown in Chinese young adults with normal occlusion, by examining CBCT digitalized images. Setting and Sample Population: Forty‐two volunteers, who presented with normal occlusion and without previous orthodontic treatment, were selected for this study. Materials and Methods: The subjects were advised to take dental CBCT and the digital images of the dentition were obtained. The widely recognized University of Southern California (USC) root vector analysis was adopted to detect the angulation and inclination of the whole tooth, as well as of the clinical crown. Results: No statistically significant difference was detected between male and female subjects. The fluctuations of the angulation and the inclination of the whole tooth from anterior to posterior in both arches manifested distinctive trends. The changes in maxillary dentition seem relatively marked, whereas those in mandibular dentition show less obvious, demonstrating moderate fluctuation both in angulation or inclination. The angulation and inclination of clinical crown are obtained and are shown positively correlated with that of each whole tooth. Conclusions: The normal range of the mesiodistal angulation and faciolingual inclination of whole tooth and clinical crown in Chinese adults with normal occlusion are identified. This study could establish clinical standards for designing 3D dental data‐based orthodontic appliances for Chinese, and for providing the guidance for orthodontic treatment.